Acute Haemodialysis-induced Changes in Tissue Doppler Echocardiography Parameters - Saim Sağ (Balkan Medical Journal, 2014)
Background: Tissue Doppler imaging (TDI) is a method that determines the tissue motion and velocity within the myocardium.